Type I Diabetes Mellitus Increases the Cardiovascular Complications of Influenza Virus Infection - Sinclair, Jane E.; Bloxham, Conor J.; Chiu, Han; Chew, Keng Yih; Russell, Jake; Yoshikawa, Yusuke; Bielefeldt-Ohmann, Helle; Steele, Lauren E.; Hulme, Katina D.; Verzele, Nathalie AJ.; Noye, Ellesandra C.; Wu, Melanie; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
People with diabetes mellitus are susceptible to both cardiovascular disease and severe influenza A virus infection. We hypothesized that diabetes also increases risks of influenza-associated cardiac complications. A murine type 1 (streptozotocin-induced) diabetes model was employed to investigate influenza-induced cardiac distress. Lung histopathology and viral titres revealed no difference in respiratory severity between infected control and diabetic mice. However, compared with infected control mice, infected diabetic mice had increased serum cardiac troponin I and creatine-kinase MB, left ventricular structural changes and right ventricular functional alterations, providing the first experimental evidence of type I diabetes increasing risks of influenza-induced cardiovascular complications.